Pre-earthquake processes : a multidisciplinary approach to earthquake prediction studies - Ouzounov, Dimitar; Pulinets, Sergey; Hattori, Katsumi; Taylor, Patrick (Washington, D.C. : American Geophysical Union ; Hoboken, NJ : John Wiley & Sons, Inc., 2018)
Pre-Earthquake signals are advanced warnings of a larger seismic event. A better understanding of these processes can help to predict the characteristics of the subsequent mainshock.Pre-Earthquake Processes: A Multidisciplinary Approach to Earthquake Prediction Studies presents the latest research on earthquake forecasting and prediction based on observations and physical modeling in China, Greece, Italy, France, Japan, Russia, Taiwan, and the United States. Volume highlights include: Describes the earthquake processes and the observed physical signals that precede them Explores the relationship between pre-earthquake activity and the characteristics of subsequent seismic events Encompasses physical, atmospheric, geochemical, and historical characteristics of pre-earthquakes Illustrates thermal infrared, seismo ionospheric, and other satellite and ground-based pre-earthquake anomalies Applies these multidisciplinary data to earthquake forecasting and prediction Written for seismologists, geophysicists, geochemists, physical scientists, students and others, Pre-Earthquake Processes: A Multidisciplinary Approach to Earthquake Prediction Studies offers an essential resource for understanding the dynamics of pre-earthquake phenomena from an international and multidisciplinary perspective.
Chapter 6 Lithosphere-Atmosphere-Ionosphere-Magnetosphere Coupling -A Concept for Pre-Earthquake Signals Generation6.1. INTRODUCTION; 6.2. LITHOSPHERE-ATMOSPHERE INTERFACE; 6.3. GEOCHEMICAL-THERMAL INTERFACE; 6.4. GEOCHEMICAL-ELECTROMAGNETIC INTERFACE; 6.5. THE SYNERGY OF EARTHQUAKE PRECURSORS AND INTEGRATED PARAMETERS; 6.6. SUMMARY AND CONCLUSIONS; ACKNOWLEDGMENTS; REFERENCES; Chapter 7 Electrical Coupling Between the Ionosphere and Surface Charges in the Earthquake Fault Zone; 7.1. PAST RESEARCH ON LITHOSPHERE-ATMOSPHERE-IONOSPHERE COUPLING MODELS
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 7, 2018).
Keywords: Earthquake prediction; Electronic books